A Systematic Review and Meta-Analysis of Cell-Based Interventions in Experimental Diabetic Kidney Disease. (9th June 2021) - Hickson, LaTonya J.; Abedalqader, Tala; Ben-Bernard, Gift; Mondy, Jayla M.; Bian, Xiaohui; Conley, Sabena M.; Zhu, Xiangyang; Herrmann, Sandra M.; Kukla, Aleksandra; Lorenz, Elizabeth C.; Kim, Seo Rin; Thorsteinsdottir, Bjorg; et al.
Abstract: Regenerative, cell-based therapy is a promising treatment option for diabetic kidney disease (DKD), which has no cure. To prepare for clinical translation, this systematic review and meta-analysis summarized the effect of cell-based interventions in DKD animal models and treatment-related factors modifying outcomes. Electronic databases were searched for original investigations applying cell-based therapy in diabetic animals with kidney endpoints (January 1998-May 2019). Weighted or standardized mean differences were estimated for kidney outcomes and pooled using random-effects models. Subgroup analyses tested treatment-related factor effects for outcomes (creatinine, urea, urine protein, fibrosis, and inflammation). In 40 studies (992 diabetic rodents), therapy included mesenchymal stem/stromal cells (MSC; 61%), umbilical cord/amniotic fluid cells (UC/AF; 15%), non-MSC (15%), and cell-derived products (13%). Tissue sources included bone marrow (BM; 65%), UC/AF (15%), adipose (9%), and others (11%). Cell-based therapy significantly improved kidney function while reducing injury markers (proteinuria, histology, fibrosis, inflammation, apoptosis, epithelial-mesenchymal-transition, oxidative stress). Preconditioning, xenotransplantation, and disease-source approaches were effective. MSC and UC/AF cells had greater effect on kidney function while cell products improved fibrosis. BM and UC/AF tissue sources more effectively improved kidney function and proteinuria vs adipose or other tissues. Cell dose, frequency, and administration route also imparted different benefits. In conclusion, cell-based interventions in diabetic animals improved kidney function and reduced injury with treatment-related factors modifying these effects. These findings may aid in development of optimal repair strategies through selective use of cells/products, tissue sources, and dose administrations to allow for successful adaptation of this novel therapeutic in human DKD. Abstract : Cell-based therapies improve diabetic kidney repair: a systematic review and meta-analysis.